Antecedents and consequents of prosperity at work: a mediation-moderation model / Antecedentes e consequentes da prosperidade no trabalho: um modelo de mediação moderada - Vladimir P. Novaes; Maria C. Ferreira; Helenides Mendonça; Cláudio V. Torres (RAM. Revista de Administração Mackenzie, 2020)
Purpose: To investigate the relationship between participation in decision making and social support at work with role performance at work, as well as the mediator role of work prosperity and the moderator role of self-efficacy.